2020
DOI: 10.1017/wsc.2020.54
|View full text |Cite
|
Sign up to set email alerts
|

Flufenacet activity is affected by GST inhibitors in blackgrass (Alopecurus myosuroides) populations with reduced flufenacet sensitivity and higher expression levels of GSTs

Abstract: The WSSA group 15 (HRAC group K3) herbicide flufenacet is a key compound in weed resistance management, primarily used for PRE control of grass-weeds in winter cereal-based crop rotations in Europe. Although resistance to compounds of its mode of action (inhibition of the synthesis of very-long chain fatty acids) generally evolves slowly, reduced flufenacet efficacy due to enhanced glutathione transferase (GST) activity has been described in several blackgrass (Alopecurus myosuroides Huds.) populations. The pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(40 citation statements)
references
References 58 publications
4
36
0
Order By: Relevance
“…These early studies suggested that enhanced metabolism driven by GSTs is the mechanism of tolerance to chloroacetanilide. Recent research on L. Rigidum and A. myosuroides resistance to pyroxasulfone and flufenacet also indicated detoxification by GSTs as the primary mechanism of resistance (Busi et al, 2018;Dücker et al, 2020). The effect of GST inhibitor on the activity of S-metolachlor on A. palmeri in our study and that of Brabham et al (2019) indicate that GSTs endow resistance to S-metolachlor in A. palmeri.…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…These early studies suggested that enhanced metabolism driven by GSTs is the mechanism of tolerance to chloroacetanilide. Recent research on L. Rigidum and A. myosuroides resistance to pyroxasulfone and flufenacet also indicated detoxification by GSTs as the primary mechanism of resistance (Busi et al, 2018;Dücker et al, 2020). The effect of GST inhibitor on the activity of S-metolachlor on A. palmeri in our study and that of Brabham et al (2019) indicate that GSTs endow resistance to S-metolachlor in A. palmeri.…”
Section: Discussionsupporting
confidence: 64%
“…The tau and phi class GST enzymes were chosen as putative candidate genes conferring resistance to S-metolachlor. To select the GST genes, we first identified the GST genes involved in VLCFA inhibitor tolerance or resistance in other species, such as Z. mays (corn), L. rigidum (rigid ryegrass) and A. myosuroides (blackgrass) from literature (Li et al, 2017a,b;Busi et al, 2018;Dücker et al, 2020). Access to recently sequenced and deposited A. palmeri genome allowed retrieval of putative homologs of such functionally related GST genes.…”
Section: Candidate Gst Genesmentioning
confidence: 99%
See 1 more Smart Citation
“…Phase II herbicide metabolism mainly involves conjugation to GSH mediated by GSH S-transferases (GSTs). Metabolic resistance to VLCFA inhibiting herbicides such as flufenacet and pyroxasulfone in Alopecurus myosuroides and L. rigidum populations is possible due to enhanced GST-mediated metabolism via differentially expressed GSTs (Dücker et al, 2019(Dücker et al, , 2020Goggin et al, 2021). In this Research Topic, empirical evidence of herbicide metabolism via CYP-450 is provided in three articles (Yanniccari, Gigón et All types of resistance mechanisms can get stacked in R plants, both TSR and NTSR, but also different genes conferring EHM.…”
Section: Recent Advances In Ntsr Mechanismsmentioning
confidence: 99%
“…Thereafter, publications on the GST-mediated resistance to multiple herbicides based on an increase in GST activity and/or gene expression were reported [11,[23][24][25][26][27][28]. Notably, detoxifying enzyme levels are greater in domesticated cereal crops than in their competing weeds; thus, these enzymes are largely responsible for differences in herbicide metabolism and selectivity [29][30][31][32][33]. Overexpression of GSTFs has been identified in A. myosuroides and L. rigidum weeds that have demonstrated herbicide tolerance.…”
Section: Introductionmentioning
confidence: 99%